Inferior outcome of stand-alone short versus long tibial stem in revision total knee arthroplasty. A retrospective comparative study with minimum 2 year follow-up - Abdelatif Elsayed Ahmed; Abu Mukh Assala; Elsaid Ahmed Nady Saleh; Youssef Ahmed Omar; Foissey Constant; Servien Elvire; Lustig Sebastien (SICOT-J)
Introduction: Revision Total Knee Arthroplasty (RTKA) is complex, and induced bone loss might endanger implant fixation and joint stability. Intramedullary stems improve fixation throughout stress redistribution. The current study aims to compare the performance of short tibial stems with long tibial stems, investigating their intermediate-term radiographic and survival outcomes in RTKA. The main hypothesis is that the two types of tibial stems would exhibit similar complication and revision rates in mid-term follow-up. Methods: Patients who underwent RTKA for all causes in a specialized arthroplasty center from 2010 to 2022 with minimum 2-year follow-up were included in this study. Patients receiving mega prosthesis or implants associated with sleeves or cones were excluded. The final groups consisted of 234 knees: 110 patients with short stems (SS) and 124 with long stems (LS). The mean age at surgery was 65.96 ± 8.73 years in SS and 67.07 ± 8.64 years in LS. The mean Body Mass Index (BMI) was 28.95 is SS and 30.88 in LS (p < 0.05). The average follow-up for SS group was 4.24 years and for LS 5.16 years (p < 0.05). Results: Complications and re-revisions did not differ significantly between two groups (p > 0.05). Pathological radiolucency was present in 20.91% in SS group and 33.87% in LS group (p < 0.02). Time-to-re-revision was shorter in SS group and occurred at a mean of 3.1 years, while LS failed at a mean of 5.1 years (p < 0.001). Conclusions: The SS and LS may be comparable in terms of complications and re-revision. SS significantly fails almost 2 years earlier than long stem (p < 0.001). Additionally, there is a higher tendency for re-revision due to loosening in patients who present pathological radiolucency in SS group. To obtain the benefits of short stem and improve the longevity of the construct; adjuvant zone II (metaphyseal) fixation might be the clue.